PERKEMBANGAN TEMA JIHAD DALAM AL-QUR’AN BERDASARKAN KRONOLOGI MEHDĪ BAZARGĀN - Muhamad Raa (Tanzil: Jurnal Studi Al-Quran, 2022)
The misunderstanding about the doctrine of jihad, especially that echoed by jihadist-extremist groups, some start from a rigid reading of the text of the Qur'an. It is obvious that there is a need for a fresh new method of reading of the verses under the theme of jihad, namely tafsir mawḍūʿī-nuzūli or thematic-chronological interpretation. Using the Qur'anic chronology introduced by Mehdī Bazargān and the periodization he worked on on the same book, followed by linguistic-lexical approach, it can be found the development of jihad verses from (1) nonviolent jihad verses, to (2) jus ad bellum, and (3) juice in bello. Also in Bazargān's chronology it can also be seen that surah Al-Tawbah [9] :5, which was known as the verses of the sword, does not abrogated previous jihad-themed verses. This is because the message of jihad is closed with a prohibition for believers to act antagonistic to those who have been hostile to them and command them to cooperate with each other in goodness and piety.